Full 3D printed graphene structure battery and preparation method thereof
The preparation of graphene structured batteries through full 3D printing technology solves the safety, energy density and manufacturing complexity of traditional batteries, and realizes efficient, safe and flexible battery design, suitable for diversified applications.
Patent Information
- Application Number
- CN202510032626.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-09
- Publication Date
- 2025-04-15
Smart Images

Figure CN119833723A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of design and preparation of graphene energy storage materials, and specifically relates to a fully 3D printed graphene structure battery and a preparation method thereof. Background Art
[0002] With the growing global demand for renewable energy and efficient energy storage devices, the development of battery technology has become an important research field. Traditional lithium-ion batteries have been widely used in portable electronic devices, electric vehicles and energy storage systems due to their high energy density and mature production process. However, traditional batteries still have many shortcomings, including but not limited to: 1. Safety issues: The use of liquid electrolytes makes traditional batteries at risk of leakage, fire and explosion under overcharge, short circuit or high temperature environment; 2. Energy density limitation: Although lithium-ion batteries perform well in terms of energy density, they still cannot meet the demanding requirements of some high-energy demand applications (such as electric vehicles and spacecraft); 3. Manufacturing complexity: The manufacturing process of traditional batteries is complex, involving multiple materials and multi-step production processes, which not only increases costs but also limits the design flexibility of batteries.
[0003] In this context, graphene, as a new type of material, has gradually attracted widespread attention from researchers due to its excellent electrical conductivity, light weight, high strength and excellent thermal conductivity. Therefore, the application of graphene provides new possibilities for the development of battery technology, especially using graphene as an electrode material, which can significantly improve the conductivity and charge and discharge rate of the battery, thereby improving the overall performance of the battery.
[0004] At the same time, the rapid development of 3D printing technology has provided new solutions for battery manufacturing. Through 3D printing, the various components of the battery can be precisely designed and manufactured, reducing material waste, simplifying the production process, and allowing flexible customization according to specific needs. This additive manufacturing method not only improves production efficiency, but also helps to integrate different materials (such as graphene, solid electrolytes, etc.) into an integrated battery structure, thereby further improving the performance and safety of the battery.
[0005] Therefore, developing a fully 3D printed graphene structure battery and its preparation method can not only overcome the drawbacks of traditional batteries, but also give full play to the superior performance of graphene and meet the needs of modern society for high-performance, low-cost and safe batteries. The innovation of this technology will provide important support for the development of next-generation flexible batteries and printable electronic devices, and has broad application potential in the field of new energy storage. Summary of the invention
[0006] In order to solve the above problems, the object of the present invention is to provide a fully 3D printed graphene structure battery and a preparation method thereof.
[0007] In order to achieve the above-mentioned purpose, the fully 3D printed graphene structure battery provided by the present invention includes a graphene current collector layer, a positive electrode material layer, a solid electrolyte layer and an integrated graphene negative electrode layer prepared by a 3D printing method and stacked together in sequence.
[0008] The graphene current collector layer is made of a slurry consisting of graphene powder, PVDF (polyvinylidene fluoride) powder and NMP (N-methylpyrrolidone) solution through 3D printing, wherein the mass ratio of graphene powder to PVDF powder is 0.8-1.2:4.6-5.4, and the solid content of the slurry is 55-65%.
[0009] The positive electrode material layer is made of a slurry consisting of lithium iron phosphate, a conductive additive, PVDF powder and an NMP solution through 3D printing, wherein the mass ratio of lithium iron phosphate, the conductive additive and the PVDF powder is 95-98:1.2-1.5:1.8-2.2, and the solid content of the slurry is 55-65%; wherein the conductive additive is selected from any one of conductive carbon black and carbon nanotubes.
[0010] The solid electrolyte layer is made of a slurry consisting of PEO (polyethylene oxide), lithium salt, oxide solid electrolyte powder and anhydrous acetonitrile through 3D printing, wherein the molar ratio of Li:EO is 1:20, 1g PEO is dissolved in 20mL anhydrous acetonitrile, and the oxide solid electrolyte accounts for 1-2% of the total weight of the slurry; wherein the lithium salt is LiTFSI (lithium trifluoromethanesulfonyl imide), and the oxide solid electrolyte powder is selected from any one of LLTO (lithium lanthanum titanate) powder and LATP (solid electrolyte) powder.
[0011] The integrated graphene negative electrode layer is made of a slurry consisting of graphene powder, carboxymethyl cellulose (CMC), styrene butadiene rubber (SBR) and deionized water through 3D printing, wherein the mass ratio of graphene powder, carboxymethyl cellulose (CMC) and styrene butadiene rubber (SBR) is 95-98:1.2-1.8:2.2-2.8, and the solid content of the slurry is 45-55%.
[0012] The method for preparing a fully 3D printed graphene structure battery provided by the present invention comprises the following steps performed in sequence:
[0013] 1) Preparation of slurry for graphene current collector layer: drying graphene powder in an oven at 80°C for at least 24 hours for use; weighing PVDF powder and dissolving it in an appropriate amount of NMP solution, stirring thoroughly until the PVDF powder is completely dissolved to prepare an NMP mixed solution, and then adding the dried graphene powder to the NMP mixed solution in multiple times, stirring continuously until the slurry is uniform without granules and flocs, and grinding until the particle size in the slurry is less than 20 μm; wherein the mass ratio of graphene powder to PVDF powder is 0.8-1.2:4.6-5.4, the solid content of the slurry is 55-65%, and the slurry is sealed with plastic wrap and stored away from light and heat;
[0014] 2) Preparation of slurry for positive electrode material layer: lithium iron phosphate, conductive additive and PVDF powder are weighed in a ratio of 95-98:1.2-1.5:1.8-2.2, PVDF powder is added to an appropriate amount of NMP solution and stirred until the PVDF powder is completely dissolved, the lithium iron phosphate and the conductive additive are mixed evenly, the mixture of lithium iron phosphate and the conductive additive is added to the PVDF mixed solution in multiple times, and stirring is continued until the slurry is free of particles and floccules, and then ground until the particle size of the particles in the slurry is less than 20 μm; wherein the solid content of the slurry is 55-65%; the slurry is sealed with plastic wrap and stored away from light and heat;
[0015] 3) Preparation of slurry for solid electrolyte layer: weigh PEO and oxide solid electrolyte powder, stir and mix for 2-3 hours to make dry powder, then slowly add the dry powder into anhydrous acetonitrile while stirring, stir for 2-3 hours at room temperature to completely dissolve PEO; weigh lithium salt and add it into the solution, stir and dissolve, put it into a defoamer for defoaming; prepare the molar ratio of Li:EO to be 1:20, dissolve 1g PEO in 20mL anhydrous acetonitrile, and the oxide solid electrolyte accounts for 1-2% of the total weight of the slurry; seal with plastic wrap and store in a refrigerator;
[0016] 4) Preparation of slurry for integrated graphene negative electrode layer: weigh carboxymethyl cellulose and add it to an appropriate amount of deionized water, stir thoroughly until the carboxymethyl cellulose is completely dissolved, then add graphene powder to the carboxymethyl cellulose solution in multiple times and continue stirring, continue to add styrene-butadiene rubber and stir until the slurry is uniform, grind until the particle size in the slurry is less than 20 μm; wherein the mass ratio of graphene: carboxymethyl cellulose: styrene-butadiene rubber is 95-98: 1.2-1.8: 2.2-2.8, and the solid content of the slurry is 45-55%; seal with plastic wrap and store away from light and heat;
[0017] 5) Take the slurry prepared in step 1) and inject it into the injection barrel of the ink direct writing printer, perform ink direct writing printing according to the designed pattern and shape, adjust the printing pressure to 350psi, the printing thickness to 50μm, complete the printing of the graphene collector layer on the printing platform, adjust the printing platform temperature to 60°C after printing, and dry the graphene collector layer; take the slurry prepared in step 2) and inject it into a new injection barrel, adjust the printing pressure to 400psi, the printing thickness to 100μm, print the positive electrode material layer on the graphene collector layer, adjust the printing platform temperature to 60°C after printing, and dry the positive electrode material. material layer; take the slurry prepared in step 3) and inject it into a new injection barrel, adjust the printing pressure to 400psi, the printing thickness to 100μm, print the solid electrolyte layer on the positive electrode material layer, adjust the printing platform temperature to 60°C after printing, and dry the solid electrolyte layer; take the slurry prepared in step 4) and inject it into a new injection barrel, adjust the printing pressure to 450psi, the printing thickness to 150μm, print an integrated graphene negative electrode layer on the solid electrolyte layer, adjust the printing platform temperature to 60°C after printing, and dry the integrated graphene negative electrode layer, thereby making a fully 3D printed graphene structure battery;
[0018] 6) Finally, the fully 3D printed graphene structure battery is packaged in the form of a soft-pack battery using an aluminum-plastic film.
[0019] Compared with the prior art, the fully 3D printed graphene structure battery and the preparation method thereof provided by the present invention have the following beneficial effects:
[0020] First, through the integrated 3D printing process, the manufacturing process is simplified, which significantly improves production efficiency and reduces costs. Secondly, the present invention allows the size and shape of the battery to be customized according to demand to meet a variety of application scenarios. In addition, the use of graphene materials enhances the conductivity and energy density of the battery and improves the charge and discharge rate. The use of solid-state electrolytes improves battery safety, reduces the risk of leakage, and achieves better thermal management. The battery can also achieve flexible and lightweight design, suitable for emerging markets such as wearable devices. In addition, 3D printing technology effectively reduces material waste, has good environmental friendliness, and due to the good stability of the material, the cycle life of the battery is also extended. These advantages make the present invention have broad application potential and market value in the field of new energy storage. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 This is a schematic diagram of a fully 3D printed graphene structure battery provided by the present invention:
[0022] Figure 2 This is a schematic diagram of the structure of the ink direct writing printer used in the present invention: DETAILED DESCRIPTION
[0023] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0024] like Figure 1 As shown, the fully 3D printed graphene structure battery provided by the present invention includes a graphene current collector layer 1, a positive electrode material layer 2, a solid electrolyte layer 3 and an integrated graphene negative electrode layer 4 which are prepared by a 3D printing method and stacked together in sequence.
[0025] The graphene current collector layer 1 is made of a slurry consisting of graphene powder, PVDF (polyvinylidene fluoride) powder and NMP (N-methylpyrrolidone) solution through 3D printing, wherein the mass ratio of graphene powder to PVDF powder is 0.8-1.2:4.6-5.4, and the solid content of the slurry is 55-65%.
[0026] The positive electrode material layer 2 is made of a slurry consisting of lithium iron phosphate, a conductive additive, PVDF powder and an NMP solution by 3D printing, wherein the mass ratio of lithium iron phosphate, the conductive additive and the PVDF powder is 95-98:1.2-1.5:1.8-2.2, and the solid content of the slurry is 55-65%; wherein the conductive additive is selected from any one of conductive carbon black and carbon nanotubes.
[0027] The solid electrolyte layer 3 is made of a slurry consisting of PEO (polyethylene oxide), lithium salt, oxide solid electrolyte powder and anhydrous acetonitrile through 3D printing, wherein the molar ratio of Li:EO is 1:20, 1g PEO is dissolved in 20mL anhydrous acetonitrile, and the oxide solid electrolyte accounts for 1-2% of the total weight of the slurry; wherein the lithium salt is LiTFSI (lithium trifluoromethanesulfonyl imide), and the oxide solid electrolyte powder is selected from any one of LLTO (lithium lanthanum titanate) powder and LATP (solid electrolyte) powder.
[0028] The integrated graphene negative electrode layer 4 is made of a slurry consisting of graphene powder, carboxymethyl cellulose (CMC), styrene butadiene rubber (SBR) and deionized water through 3D printing, wherein the mass ratio of graphene powder, carboxymethyl cellulose (CMC) and styrene butadiene rubber (SBR) is 95-98:1.2-1.8:2.2-2.8, and the solid content of the slurry is 45-55%.
[0029] Embodiment 1:
[0030] The method for preparing a fully 3D printed graphene structure battery provided in this embodiment includes the following steps performed in sequence:
[0031] 1) Preparation of slurry of graphene current collector layer 1: drying graphene powder in an oven at 80°C for at least 24 hours for use; weighing PVDF powder and dissolving it in an appropriate amount of NMP solution, stirring thoroughly until the PVDF powder is completely dissolved to prepare an NMP mixed solution, and then adding the dried graphene powder to the NMP mixed solution in multiple times, stirring continuously until the slurry is uniform without granules and flocs, and grinding until the particle size of the particles in the slurry is less than 20 μm; wherein the mass ratio of graphene powder to PVDF powder is 0.8:4.6, the solid content of the slurry is 55%, and the slurry is sealed with plastic wrap and stored away from light and heat;
[0032] 2) Preparation of slurry for positive electrode material layer 2: lithium iron phosphate, conductive carbon black and PVDF powder are weighed in a ratio of 95:1.2:1.8, PVDF powder is added to an appropriate amount of NMP solution and stirred until the PVDF powder is completely dissolved, lithium iron phosphate and conductive carbon black are mixed evenly, the mixture of lithium iron phosphate and conductive carbon black is added to the PVDF mixed solution in multiple times, and stirring is continued until the slurry is free of particles and floccules, and then ground until the particle size of the particles in the slurry is less than 20 μm; wherein the solid content of the slurry is 55%; sealed with plastic wrap and stored away from light and heat;
[0033] 3) Preparation of slurry for solid electrolyte layer 3: PEO and oxide solid electrolyte powder are weighed, stirred and mixed for 2 hours to form dry powder, and then the dry powder is slowly added to anhydrous acetonitrile under stirring, and stirred at room temperature for 3 hours to completely dissolve PEO; LiTFSI is weighed and added to the solution, stirred to dissolve, and placed in a defoamer for defoaming; the molar ratio of Li:EO is prepared to be 1:20, 1g PEO is dissolved in 20mL anhydrous acetonitrile, and the oxide solid electrolyte accounts for 1% of the total weight of the slurry; it is sealed with plastic wrap and refrigerated for storage;
[0034] 4) Preparation of slurry of integrated graphene negative electrode layer 4: weigh carboxymethyl cellulose and add it to an appropriate amount of deionized water, stir thoroughly until the carboxymethyl cellulose is completely dissolved, then add graphene powder to the carboxymethyl cellulose solution in multiple times and continue stirring, continue to add styrene-butadiene rubber and stir until the slurry is uniform, grind until the particle size in the slurry is less than 20 μm; wherein the mass ratio of graphene: carboxymethyl cellulose: styrene-butadiene rubber is 95:1.2:2.2, and the solid content of the slurry is 45%; seal with plastic wrap and store away from light and heat;
[0035] 5) If Figure 2As shown, the slurry prepared in step 1) is taken and injected into the injection barrel of the ink direct writing printer, and the ink direct writing printing is performed according to the designed pattern and shape, the printing pressure is adjusted to 350psi, the printing thickness is 50μm, and the printing of the graphene collector layer 1 is completed on the printing platform. After the printing is completed, the temperature of the printing platform is adjusted to 60°C, and the graphene collector layer 1 is dried; the slurry prepared in step 2) is taken and injected into a new injection barrel, the printing pressure is adjusted to 400psi, the printing thickness is 100μm, and the positive electrode material layer 2 is printed on the graphene collector layer 1. After the printing is completed, the temperature of the printing platform is adjusted to 60°C, and the positive electrode material is dried. Layer 2; take the slurry prepared in step 3) and inject it into a new injection barrel, adjust the printing pressure to 400psi, the printing thickness to 100μm, print the solid electrolyte layer 3 on the positive electrode material layer 2, adjust the printing platform temperature to 60°C after printing, and dry the solid electrolyte layer 3; take the slurry prepared in step 4) and inject it into a new injection barrel, adjust the printing pressure to 450psi, the printing thickness to 150μm, print an integrated graphene negative electrode layer 4 on the solid electrolyte layer 3, adjust the printing platform temperature to 60°C after printing, and dry the integrated graphene negative electrode layer 4, thereby making a fully 3D printed graphene structure battery;
[0036] 6) Finally, the fully 3D printed graphene structure battery is packaged in the form of a soft-pack battery using an aluminum-plastic film.
[0037] Embodiment 2:
[0038] The method for preparing a fully 3D printed graphene structure battery provided in this embodiment includes the following steps performed in sequence:
[0039] 1) Preparation of slurry of graphene current collector layer 1: drying graphene powder in an oven at 80°C for at least 24 hours for use; weighing PVDF powder and dissolving it in an appropriate amount of NMP solution, stirring thoroughly until the PVDF powder is completely dissolved to prepare an NMP mixed solution, and then adding the dried graphene powder to the NMP mixed solution in multiple times, stirring continuously until the slurry is uniform without granules and flocs, and grinding until the particle size of the particles in the slurry is less than 20 μm; wherein the mass ratio of graphene powder to PVDF powder is 1.2:5.4, the solid content of the slurry is 65%, and the slurry is sealed with plastic wrap and stored away from light and heat;
[0040] 2) Preparation of slurry for positive electrode material layer 2: lithium iron phosphate, carbon nanotubes and PVDF powder are weighed in a ratio of 98:1.5:2.2, PVDF powder is added to an appropriate amount of NMP solution and stirred until the PVDF powder is completely dissolved, lithium iron phosphate and carbon nanotubes are mixed evenly, the mixture of lithium iron phosphate and carbon nanotubes is added to the PVDF mixed solution in multiple times, and stirring is continued until the slurry is free of particles and floccules, and then ground until the particle size of the particles in the slurry is less than 20 μm; wherein the solid content of the slurry is 65%; sealed with plastic wrap and stored away from light and heat;
[0041] 3) Preparation of slurry for solid electrolyte layer 3: PEO and oxide solid electrolyte powder are weighed, stirred and mixed for 3 hours to form dry powder, and then the dry powder is slowly added to anhydrous acetonitrile under stirring, and stirred at room temperature for 3 hours to completely dissolve PEO; LiTFSI is weighed and added to the solution, stirred to dissolve, and placed in a defoamer for defoaming; the molar ratio of Li:EO is prepared to be 1:20, 1g PEO is dissolved in 20mL anhydrous acetonitrile, and the oxide solid electrolyte accounts for 2% of the total weight of the slurry; it is sealed with plastic wrap and refrigerated for storage;
[0042] 4) Preparation of slurry of integrated graphene negative electrode layer 4: weigh carboxymethyl cellulose and add it to an appropriate amount of deionized water, stir thoroughly until the carboxymethyl cellulose is completely dissolved, then add graphene powder to the carboxymethyl cellulose solution in multiple times and continue stirring, continue to add styrene-butadiene rubber and stir until the slurry is uniform, grind until the particle size in the slurry is less than 20 μm; wherein the mass ratio of graphene: carboxymethyl cellulose: styrene-butadiene rubber is 98:1.8:2.8, and the solid content of the slurry is 55%; seal with plastic wrap and store away from light and heat;
[0043] 5) Take the slurry prepared in step 1) and inject it into the injection barrel of the ink direct writing printer, perform ink direct writing printing according to the designed pattern and shape, adjust the printing pressure to 350psi, the printing thickness to 50μm, complete the printing of the graphene collector layer 1 on the printing platform, adjust the printing platform temperature to 60°C after printing, and dry the graphene collector layer 1; Take the slurry prepared in step 2) and inject it into a new injection barrel, adjust the printing pressure to 400psi, the printing thickness to 100μm, print the positive electrode material layer 2 on the graphene collector layer 1, adjust the printing platform temperature to 60°C after printing, and dry the positive electrode material Layer 2; take the slurry prepared in step 3) and inject it into a new injection barrel, adjust the printing pressure to 400psi, the printing thickness to 100μm, print the solid electrolyte layer 3 on the positive electrode material layer 2, adjust the printing platform temperature to 60°C after printing, and dry the solid electrolyte layer 3; take the slurry prepared in step 4) and inject it into a new injection barrel, adjust the printing pressure to 450psi, the printing thickness to 150μm, print an integrated graphene negative electrode layer 4 on the solid electrolyte layer 3, adjust the printing platform temperature to 60°C after printing, and dry the integrated graphene negative electrode layer 4, thereby making a fully 3D printed graphene structure battery;
[0044] 6) Finally, the fully 3D printed graphene structure battery is packaged in the form of a soft-pack battery using an aluminum-plastic film.
[0045] Embodiment 3:
[0046] The method for preparing a fully 3D printed graphene structure battery provided in this embodiment includes the following steps performed in sequence:
[0047] 1) Preparation of slurry of graphene current collector layer 1: drying graphene powder in an oven at 80°C for at least 24 hours for use; weighing PVDF powder and dissolving it in an appropriate amount of NMP solution, stirring thoroughly until the PVDF powder is completely dissolved to prepare an NMP mixed solution, and then adding the dried graphene powder to the NMP mixed solution in multiple times, stirring continuously until the slurry is uniform without granules and flocs, and grinding until the particle size of the particles in the slurry is less than 20 μm; wherein the mass ratio of graphene powder to PVDF powder is 1.0:5.0, the solid content of the slurry is 60%, and the slurry is sealed with plastic wrap and stored away from light and heat;
[0048] 2) Preparation of slurry for positive electrode material layer 2: lithium iron phosphate, conductive carbon black and PVDF powder are weighed in a ratio of 96:1.4:2.0, PVDF powder is added to an appropriate amount of NMP solution and stirred until the PVDF powder is completely dissolved, lithium iron phosphate and conductive carbon black are mixed evenly, the mixture of lithium iron phosphate and conductive carbon black is added to the PVDF mixed solution in multiple times, and stirring is continued until the slurry is free of particles and floccules, and then ground until the particle size of the particles in the slurry is less than 20 μm; wherein the solid content of the slurry is 60%; sealed with plastic wrap and stored away from light and heat;
[0049] 3) Preparation of slurry for solid electrolyte layer 3: PEO and oxide solid electrolyte powder are weighed, stirred and mixed for 2 hours to form dry powder, and then the dry powder is slowly added to anhydrous acetonitrile under stirring, and stirred at room temperature for 2 hours to completely dissolve PEO; LiTFSI is weighed and added to the solution, stirred to dissolve, and placed in a defoamer for defoaming; the molar ratio of Li:EO is prepared to be 1:20, 1g PEO is dissolved in 20mL anhydrous acetonitrile, and the oxide solid electrolyte accounts for 1.5% of the total weight of the slurry; it is sealed with plastic wrap and refrigerated for storage;
[0050] 4) Preparation of slurry of integrated graphene negative electrode layer 4: weigh carboxymethyl cellulose and add it to an appropriate amount of deionized water, stir thoroughly until the carboxymethyl cellulose is completely dissolved, then add graphene powder to the carboxymethyl cellulose solution in multiple times and continue stirring, continue to add styrene-butadiene rubber and stir until the slurry is uniform, grind until the particle size in the slurry is less than 20 μm; wherein the mass ratio of graphene: carboxymethyl cellulose: styrene-butadiene rubber is 97:1.5:2.5, and the solid content of the slurry is 50%; seal with plastic wrap and store away from light and heat;
[0051] 5) Take the slurry prepared in step 1) and inject it into the injection barrel of the ink direct writing printer, perform ink direct writing printing according to the designed pattern and shape, adjust the printing pressure to 350psi, the printing thickness to 50μm, complete the printing of the graphene collector layer 1 on the printing platform, adjust the printing platform temperature to 60°C after printing, and dry the graphene collector layer 1; Take the slurry prepared in step 2) and inject it into a new injection barrel, adjust the printing pressure to 400psi, the printing thickness to 100μm, print the positive electrode material layer 2 on the graphene collector layer 1, adjust the printing platform temperature to 60°C after printing, and dry the positive electrode material Layer 2; take the slurry prepared in step 3) and inject it into a new injection barrel, adjust the printing pressure to 400psi, the printing thickness to 100μm, print the solid electrolyte layer 3 on the positive electrode material layer 2, adjust the printing platform temperature to 60°C after printing, and dry the solid electrolyte layer 3; take the slurry prepared in step 4) and inject it into a new injection barrel, adjust the printing pressure to 450psi, the printing thickness to 150μm, print an integrated graphene negative electrode layer 4 on the solid electrolyte layer 3, adjust the printing platform temperature to 60°C after printing, and dry the integrated graphene negative electrode layer 4, thereby making a fully 3D printed graphene structure battery;
[0052] 6) Finally, the fully 3D printed graphene structure battery is packaged in the form of a soft-pack battery using an aluminum-plastic film.
Claims
1. A fully 3D printed graphene structure battery, characterized in that: The graphene structure battery comprises a graphene current collector layer (1), a positive electrode material layer (2), a solid electrolyte layer (3) and an integrated graphene negative electrode layer (4) which are prepared by a 3D printing method and stacked in sequence.
2. The fully 3D printed graphene structure battery according to claim 1, characterized in that: The graphene current collector layer (1) is made of a slurry consisting of graphene powder, PVDF powder and NMP solution through 3D printing, wherein the mass ratio of graphene powder to PVDF powder is 0.8-1.2:4.6-5.4, and the solid content of the slurry is 55-65%.
3. The fully 3D printed graphene structure battery according to claim 1, characterized in that: The positive electrode material layer (2) is made of a slurry consisting of lithium iron phosphate, a conductive additive, PVDF powder and an NMP solution through 3D printing, wherein the mass ratio of lithium iron phosphate, the conductive additive and the PVDF powder is 95-98:1.2-1.5:1.8-2.2, and the solid content of the slurry is 55-65%; wherein the conductive additive is selected from any one of conductive carbon black and carbon nanotubes.
4. The fully 3D printed graphene structure battery according to claim 1, characterized in that: The solid electrolyte layer (3) is made of a slurry consisting of PEO, lithium salt, oxide solid electrolyte powder and anhydrous acetonitrile through 3D printing, wherein the molar ratio of Li:EO is 1:20, 1g PEO is dissolved in 20mL anhydrous acetonitrile, and the oxide solid electrolyte accounts for 1-2% of the total weight of the slurry; wherein the lithium salt is LiTFSI, and the oxide solid electrolyte powder is selected from any one of LLTO powder and LATP powder.
5. The fully 3D printed graphene structure battery according to claim 1, characterized in that: The integrated graphene negative electrode layer (4) is made of a slurry consisting of graphene powder, carboxymethyl cellulose, styrene butadiene rubber and deionized water through 3D printing, wherein the mass ratio of graphene powder, carboxymethyl cellulose and styrene butadiene rubber is 95-98:1.2-1.8:2.2-2.8, and the solid content of the slurry is 45-55%.
6. A method for preparing a fully 3D printed graphene structure battery as claimed in any one of claims 1 to 5, characterized in that: The preparation method comprises the following steps performed in sequence: 1) Preparation of slurry of graphene current collector layer (1): drying graphene powder in an oven at 80° C. for at least 24 hours for use; weighing PVDF powder and dissolving it in an appropriate amount of NMP solution, stirring thoroughly until the PVDF powder is completely dissolved to prepare an NMP mixed solution, then adding the dried graphene powder to the NMP mixed solution in multiple times, stirring continuously until the slurry is uniform and free of particles and flocs, grinding until the particle size of the particles in the slurry is less than 20 μm; wherein the mass ratio of graphene powder to PVDF powder is 0.8-1.2:4.6-5.4, the solid content of the slurry is 55-65%, and the slurry is sealed with plastic wrap and stored away from light and heat; 2) Preparation of slurry for the positive electrode material layer (2): lithium iron phosphate, conductive additive and PVDF powder are weighed in a ratio of 95-98:1.2-1.5:1.8-2.2, PVDF powder is added to an appropriate amount of NMP solution and stirred thoroughly until the PVDF powder is completely dissolved, the lithium iron phosphate and the conductive additive are mixed evenly, the mixture of lithium iron phosphate and the conductive additive is added to the PVDF mixed solution in multiple times, and stirring is continued until the slurry is free of particles and flocs, and then ground until the particle size of the particles in the slurry is less than 20 μm; The slurry has a solid content of 55-65%; the slurry is sealed with plastic wrap and stored away from light and heat; 3) Preparation of slurry for solid electrolyte layer (3): PEO and oxide solid electrolyte powder are weighed, stirred and mixed for 2-3 hours to prepare dry powder, and then the dry powder is slowly added into anhydrous acetonitrile under stirring, and stirred at room temperature for 2-3 hours to completely dissolve PEO; lithium salt is weighed and added into the solution, stirred to dissolve, and placed in a defoamer for defoaming; the molar ratio of Li:EO is prepared to be 1:20, 1g PEO is dissolved in 20mL anhydrous acetonitrile, and the oxide solid electrolyte accounts for 1-2% of the total weight of the slurry; the slurry is sealed with plastic wrap and stored in a refrigerator; 4) Preparation of slurry of integrated graphene negative electrode layer (4): weigh carboxymethyl cellulose and add it to an appropriate amount of deionized water, stir thoroughly until the carboxymethyl cellulose is completely dissolved, then add graphene powder to the carboxymethyl cellulose solution in multiple times and continue stirring, continue to add styrene-butadiene rubber and stir until the slurry is uniform, grind until the particle size of the slurry is less than 20 μm; wherein the mass ratio of graphene: carboxymethyl cellulose: styrene-butadiene rubber is 95-98: 1.2-1.8: 2.2-2.8, and the solid content of the slurry is 45-55%; seal with plastic wrap and store away from light and heat; 5) Take the slurry prepared in step 1) and inject it into the injection barrel of the ink direct writing printer, perform ink direct writing printing according to the designed pattern and shape, adjust the printing pressure to 350psi, the printing thickness to 50μm, complete the printing of the graphene current collector layer (1) on the printing platform, adjust the printing platform temperature to 60°C after printing, and dry the graphene current collector layer (1); take the slurry prepared in step 2) and inject it into a new injection barrel, adjust the printing pressure to 400psi, the printing thickness to 100μm, print the positive electrode material layer (2) on the graphene current collector layer (1), adjust the printing platform temperature to 60°C after printing, and dry the positive electrode material layer (2) ); take the slurry prepared in step 3) and inject it into a new injection barrel, adjust the printing pressure to 400psi, the printing thickness to 100μm, print the solid electrolyte layer (3) on the positive electrode material layer (2), adjust the printing platform temperature to 60°C after printing, and dry the solid electrolyte layer (3); take the slurry prepared in step 4) and inject it into a new injection barrel, adjust the printing pressure to 450psi, the printing thickness to 150μm, print an integrated graphene negative electrode layer (4) on the solid electrolyte layer (3), adjust the printing platform temperature to 60°C after printing, and dry the integrated graphene negative electrode layer (4), thereby making a fully 3D printed graphene structure battery; 6) Finally, the fully 3D printed graphene structure battery is packaged in the form of a soft-pack battery using an aluminum-plastic film.